2019
DOI: 10.14202/vetworld.2019.1078-1084
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia enterocolitica: Prevalence, virulence, and antimicrobial resistance from retail and processed meat in Egypt

Abstract: Aim: The objectives of this study were to investigate the prevalence of Yersinia enterocolitica in retail chicken meat, ground and processed beef meat, determine their virulence-associated genes, antimicrobial susceptibility pattern, molecular detection of extended-spectrum β-lactamases, and their capability of biofilm formation in vitro. Materials and Methods: A total of 210 samples (120 retail chicken meat, 30 ground beef, 30 beef burger, and 30 sausage samples) were collected from different retail chicken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
5
13
1
1
Order By: Relevance
“…In our study, 61.9% of the isolates showed antimicrobial resistance, with an increase from 2013 to 2017. Similar results were obtained in Egypt [ 48 ]. In 31 Bavarian farms from 2000 to 2004, a study on Ye strains showed that 77% of 4/O:3 strains were sensitive to 14 antimicrobial drugs [ 50 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, 61.9% of the isolates showed antimicrobial resistance, with an increase from 2013 to 2017. Similar results were obtained in Egypt [ 48 ]. In 31 Bavarian farms from 2000 to 2004, a study on Ye strains showed that 77% of 4/O:3 strains were sensitive to 14 antimicrobial drugs [ 50 ].…”
Section: Discussionsupporting
confidence: 90%
“…A small percentage of the isolates was positive for myfA and inv (11.9 and 7.9%, respectively). In our study, we outlined a major presence of ail and yst genes with respect to the study conducted by Younis and coworkers in Egypt [ 48 ]. Our results showed the presence of ystB both in 1A and 1B biotypes; therefore, on the basis of Liang et al’sassumptions [ 45 ], it could be speculated that both 1A and 1B biotype strains are pathogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results in MDR Y. enterocolitica isolates were observed by many investigators (Bonardi et al, 2010;Thong et al, 2018). Younis et al (2019) identified a low prevalence of MDR Y. enterocolitica isolates (23.33%) from retail and processed meat in Egypt, while Ye et al (2015) and Peng et al (2018) demonstrated the high occurrence of MDR Y. enterocolitica strains (94.3%, 92.3%) in China, respectively. There are many reasons for the elevation of percentages of multidrug-resistant pathogenic bacterium including the illegal and inaccurate prescription of antibiotics, the long term use and even abuse of feed antibiotics (Dehkordi et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Our results showed that the capacity to form biofilms among the Y. enterocolitica examined strains could be a strain‐related feature. Although, some authors reported that all Y. enterocolitica strains examined in their studies had produced biofilms(Ioannidis et al 2014; Singhal et al 2019), our results are in accordance with other studies that showed differences in biofilm formation among the examined strains (Wang et al 2017; Zadernowska and Chajęcka‐Wierzchowska 2017; Younis et al 2019).…”
Section: Discussionsupporting
confidence: 91%